Can Auditory Stimulation Improve Sleep Apnea? - Kranz Dominik D.; Salanitro Matthew; Osmers Eike; Rosenblum Lisa; Schöbel Christoph; Kolossa Dorothea; Penzel Thomas; Wessel Niels (Current Directions in Biomedical Engineering)
Recent advancements in the field of acoustic stimulation have shown promising effects on the autonomic nervous system, influencing parameters such as heart rate [1] and cognitive performance [2]. In this study, we analyzed polygraphy data from patients with heart failure related central sleep apnea. We compared the Apnea-Hypopnea Index (AHI) during a baseline night with that during a night where acoustic stimulation was applied for 40 minutes before bedtime. Seven out of eight patients showed a significant reduction in AHI during the intervention night (p < 0.01). These preliminary findings suggest that further investigation in a more controlled environment is warranted.